The Effect of Cultural Context on Understanding the Prophetic Hadith - Mhesen, Rania Jasim (Journal of Ecohumanism, 2025)
Prophetic Hadith is the second source of Islamic legislation, and its understanding is influenced by the surrounding cultural and social context. The research aims to study the effect of cultural context on the explanation of Prophetic Hadith, with a focus on how to adapt their understanding to fit modern changes without affecting the objectives of Islamic law. The research deals with the concept of cultural context, its components such as language, customs and traditions, and how this context affects the understanding and application of texts across the ages. It also discusses the influence of cultural context in the early, medieval and modern Islamic eras, explaining how cultural and social changes affect the interpretation of Prophetic Hadith. The research concludes by emphasizing the importance of taking into account the cultural context to ensure an accurate interpretation that is in line with contemporary challenges without prejudice to Islamic values.